Determinants of Land Tenure Contracts; Theory and Evidence from Rural India - Ananish Chaudhuri; Pushkar Maitra (Rutgers University, Department of Economics, 1997)
In this paper we analyze the factors that affect the choice of land tenure contracts in the semi arid tropics of India. We develop a dynamic principal-agent model with one-sided private information to explain the co-existence of wage, rent and share-cropping contracts. We generate empirically testable hypotheses about how multiple contracts can co-exist and we identify household and plot level characteristics that explain such co-existence. Using plot level data from three Indian villages we find that increasing the age of the head of the cultivating household and the value of the plot under cultivation increases the probability that the plot is under tenant cultivation (i.e. cultivated under a share or rent contract).
Keywords: O12; C35; D82; 330; Principal-agent; Qualitative dependent variable; Share-cropping; Tenurial contracts